PENGARUH KUALITAS LAYANAN DAN VARIASI MENU TERHADAP KEPUASAN KONSUMEN DIMODERASI OLEH ATMOSFER CAFE NIWA CANTING - Scorina Dwiantari; Irene Nathalia Setiawan; Bambang Heriawan (JURNAL ILMIAH EDUNOMIKA, 2025)
The growth of the culinary business is increasing in line with the growth of people's lifestyles, work patterns, and income increases, especially in communities close to urban areas. Hanging out in cafes has become a habit for Indonesian people. This finally encourages business people to pioneer a business in the culinary field in the form of cafes. By creating an attractive cafÃ© atmosphere, the service that consumers can expect and a complete variety of menus will cause satisfaction in the hearts of consumers so that consumers can revisit repeatedly. The purpose of this study is to find out how much influence the quality of service and menu variety moderated by the cafÃ© atmosphere on consumer satisfaction. The sampling technique uses purposive sampling. Data collection method using questionnaire and data analysis technique using Smart PLS